What Drives the High Price of Road Freight Transport in Central America? - Osborne, Theresa (World Bank, Washington, DC, 2014)
In Central America, like many other developing regions, high transport costs are cited as an impediment to trade and economic growth. Prices for road freight transport -- a key mode of transport comprising a significant share of total transport costs for intra- and extra-regional trade, are particularly high. Averaging 17 cents per ton-kilometer on main trading routes, these rates stand out even relative to other inefficient developing country markets (e.g., central and west Africa). However, the policy and other factors associated with increased prices have not been well understood. This paper uses data from a survey of trucking companies operating on the region's main trade corridors to analyze the determinants of firms' costs of providing service, as well as the effect of market structure and competition on prices. The analysis finds that whereas improved cost efficiencies could reduce prices by 3 cents per ton-kilometer, increased competition on national routes -- those entirely within a nation's borders -- would reduce prices by significantly more. Although there are many trucking companies, including small and somewhat informal operators, the degree of competition varies by route because of domestic restraints on competition and the prohibition on international competition on national routes. The paper shows empirically that imperfect competition accounts for at least 35 percent of mean prices on national routes. In addition, a lack of competition is likely to explain the persistence of an inefficient market structure, as well as a lack of innovation to reduce costs and enhance the quality of service.